2011
DOI: 10.1016/s1015-9584(11)60012-2
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Resection of Mediastinal Bronchogenic Cysts in Adults

Abstract: Thoracoscopic resection of mediastinal bronchogenic cyst is minimally invasive and has no serious postoperative complications, and should therefore be considered as the primary therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…According to some reported studies, the conversion rate from VATS to open thoracotomy was 8-35%, and the main reason was major pleural adhesion (4,6,14). However, in our institution, VATS was initially performed in patients with lung cancer and some benign lung diseases, such as pneumothorax, tuberculous, and pulmonary aspergillosis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…According to some reported studies, the conversion rate from VATS to open thoracotomy was 8-35%, and the main reason was major pleural adhesion (4,6,14). However, in our institution, VATS was initially performed in patients with lung cancer and some benign lung diseases, such as pneumothorax, tuberculous, and pulmonary aspergillosis.…”
Section: Discussionmentioning
confidence: 91%
“…Four cysts were projected as waterlike on MRI while they were all seen as soft-tissue-like on CT images, which demonstrated that MRI may be useful for differentiating MBC from mediastinal neoplasia when CT scans manifest as soft-tissue-like lesions. For patients exhibiting symptoms, surgical resection is the preferred treatment modality (14). Other treatment modalities, such as robotic thoracic surgery and endobronchial ultrasound-guided transbronchial needle aspiration (15,16), are still in the developmental stages, and follow-up is still needed to verify the long-term efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the discovery of the tumor on the chest radiograph, the diagnostic process should be supplemented with a CT or MRI scan of the chest, which is not only helpful in reaching the diagnosis and determining the tumor’s relation to adjacent organs, but also provides an opportunity to select appropriate treatment methods and strategies [1, 2, 6]. Establishing the precise location of the tumor and its relations to adjacent structures is very important in anticipating potential intraoperative difficulties: it facilitates adequate preparation of the patient for surgery and efficient trocar placement [2, 9, 10]. The management of mediastinal cysts is a topic of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…They are thought to originate from abnormal embryogenesis between the 4 th and 8 th week of gestation [2]. Bronchogenic cysts can cause symptoms such as persistent cough, hoarseness, recurrent pneumonia, and – in the case of large tumors pressing on the adjacent organs of the mediastinum – dyspnea, acute respiratory failure, difficulty in swallowing, superior vena cava syndrome, and Horner’s syndrome.…”
Section: Introductionmentioning
confidence: 99%